Schizophasia and Cognitive Impairment in Schizophrenia: A Literature Review - Sylwia Niedźwiadek; Agata Szulc (Brain Sciences)
Background: Cognitive functions are the basis for the development of language skills. Cognitive disorders occur in schizophrenia and may be present even before the first symptoms of psychosis. Language deficits are also mentioned as one of the diagnostic symptoms of this disease. Methods: A literature search was performed using the PubMed database. Articles comparing linguistic and cognitive functioning in schizophrenia were searched for. Following the inclusion and exclusion criteria, twenty-six original articles were selected. Results: Most studies have observed a partial correlation between language and cognitive deficits. The correlation most often involved some cognitive functions or some components of language assessment. Conclusions: The correlation reported in many studies shows that there is a correlation between language and cognitive deficits in schizophrenia. However, numerous studies contradict these reports. It is, therefore, possible that this correlation exists, but not in all patients. Future research should therefore be aimed at identifying in which patients this correlation is present.